Clonal Propagation and Karyomorphological Study of Solanum torvum Swartz: An Ethnobotanical Species of Tripura, India (Plant Tissue Culture and Biotechnology, 2018)
An efficient method of clonal propagation through nodal culture of Solanum torvum Swartz. is described. Different concentrations of BAP/Kn alone or in combination with IAA were tested for direct shoot bud induction and proliferation. Lower concentration of BAP/Kn alone produced better shoot proliferation and elongation. Maximum number of shoot proliferation was achieved from MS supplemented with Kn 0.5 mg/l with an average 4.0 ± 1.41 shoots during 28 days of culture. Addition of IAA to the culture media in combination with BAP/ Kn significantly reduced the number of shoot formation. Regenerated plants also produced roots during subsequent culture in the same media supplemented with BAP/Kn alone or in combination with IAA. The easy nature of in vitro rooting of S. torvum was recorded without any separate root induction phase. Regenerated plants were successfully transferred to the field condition. Clonal feature was cytologically confirmed through the study of mitotic metaphase chromosomes of regenerated plants which reveals 2n = 24 somatic chromosomes. Comparative karyomorphological details between the mother and regenerated plants of S. torvum revealed close similarity in their chromosomal complements and falls under the category of "1B" Stebbin’s symmetric index suggesting true to type nature of the regenerated plant.Plant Tissue Cult. & Biotech. 28(1): 69-76, 2018 (June)